Breaking the boundaries of professional regulation: medical licensing, foreign influence, and the consolidation of homeopathy in Mexico - Jethro Hernández Berrones (História, Ciências, Saúde: Manguinhos)
Abstract As doctors sought state support to regulate professional training and practice after Independence, Mexicans also developed different attitudes toward foreign ideas, influences, and professionals. Leveraging the allure of the foreign among Mexicans, homeopaths strategically used work, products, and organizations from abroad to establish their practices and fight changing professional policies in the country that threatened homeopathic institutions. Homeopaths inhabited the blurry and shifting boundary between professional and lay medical practice during the early Republican period, the Porfiriato, and the post-revolutionary era, and used the ambivalent feelings about medical licensing, and foreign influence in Mexican society to consolidate their position.